Zone‐specific gene expression patterns in articular cartilage. Issue 2 (28th January 2013) - Grogan, Shawn P.; Duffy, Stuart F.; Pauli, Chantal; Koziol, James A.; Su, Andrew I.; D'Lima, Darryl D.; Lotz, Martin K.
Abstract: Objective: To identify novel genes and pathways specific to the superficial zone (SZ), middle zone (MZ), and deep zone (DZ) of normal articular cartilage. Methods: Articular cartilage was obtained from the knees of 4 normal human donors. The cartilage zones were dissected on a microtome. RNA was analyzed on human genome arrays. The zone‐specific DNA array data obtained from human tissue were compared to array data obtained from bovine cartilage. Genes differentially expressed between zones were evaluated using direct annotation for structural or functional features, and by enrichment analysis for integrated pathways or functions. Results: The greatest differences in genome‐wide RNA expression data were between the SZ and DZ in both human and bovine cartilage. The MZ, being a transitional zone between the SZ and DZ, thereby shared some of the same pathways as well as structural/functional features of the adjacent zones. Cellular functions and biologic processes that were enriched in the SZ relative to the DZ included, most prominently, extracellular matrix–receptor interactions, cell adhesion molecule functions, regulation of actin cytoskeleton, ribosome‐related functions, and signaling aspects such as the IFN, IL4, Cdc42/Rac, and JAK/STAT signaling pathways. Two pathways were enriched in the DZ relative to the SZ, including PPARG and EGFR/SMRTE. Conclusion: These differences in cartilage zonal gene expression identify new markers and pathways that govern the unique differentiation status of chondrocyte subpopulations.